Does optimal follicular size in IUI cycles vary between clomiphene citrate and gonadotrophins treatments?. (February 2014) - Shalom-Paz, Einat; Marzal, Alicia; Wiser, Amir; Hyman, Jordana; Tulandi, Togas
Abstract Objective: To evaluate pregnancy-related leading follicles during ovulation induction and superovulation with clomiphene citrate (CC) or gonadotropin. Design: Retrospective cohort. Patients: Five hundred and forty-two women who underwent a total of 615 treatment cycles with CC or gonadotropin. Intervention: We evaluated the effects of CC and gonadotropin on the leading follicles, clinical pregnancy rates and miscarriage rate. Results: The number of follicles larger than 15 mm in the different protocols was comparable. In those treated with CC, the diameter of the dominant follicles before human chorionic gonadotropins (hCG) trigger in the conception cycles (20.4 ± 1.2 mm) was significantly larger than in the non-conception cycles (18.8 ± 1.9 mm). In women treated with gonadotropin, the diameter of the leading follicle in the conception cycles (18.5 ± 1.7 mm) was comparable to that in the non-conception cycles (18.2 ± 1.7 mm). The pregnancy-related diameter of the leading follicle in CC cycles (20.4 ± 1.2 mm) was significantly larger than that in gonadotropin cycles (18.8 ± 1.9 mm; p = 0.001; 95% CI, −2.2 to −0.9). Conclusion: Pregnancy-related diameter of the leading follicle in CC cycles is significantly larger than that in gonadotropin cycles and the best time for hCG trigger in the CC cycle is when the leading follicle reaches 20 mm.